EVALUASI PENGGUNAAN OBAT ANTITUBERKULOSIS (OAT) PADA PASIEN TB PARU DI PUSKESMAS PUNGGUR KABUPATEN LAMPUNG TENGAH PERIODE OKTOBER 2022 - OKTOBER 2023 - Akhmad Rokiban; Kiky Maykasari (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Tuberculosis is a infectious chronic disease caused by Mycobacterium tuberculosis. Based on WHO data the incidence of tuberculosis in Indonesia reached 842 thousand cases with a mortality rate of 107 thousand cases. To eradicate tuberculosis, one of which can be realized by the use of antituberculosis drugs by National Guidelines Standards. The purpose of this study was to evaluate the suitability of the use of OAT for pulmonary tuberculosis patients in Punggur Public Health Center, Central Lampung Regency from October 2022 - October 2023 based on the